Rigging Norse Ships in Vinland, ca. 1000 AD: The Halyard Block - Sayers, William (The Northern Mariner / Le marin du nord, 2024)
Historical, archaeological, narrative, iconographical, and philological evidence, along with technical reasoning, is brought to bear on the terminology for what appears a vital piece of rigging gear on early Norse ships. Called a húsasnotra or simply snotra, the object is here identified as an encased halyard block, mounted, knob-like, at the top of the mast above the ship’s single square sail. The burl from a hardwood like a maple (explicitly named in narrative texts), with its dense, swirling grain, would have been suitable material for the housing and would provide an attractive ornamental effect at a prominent spot on war ships and cargo ships from about the year 1000 AD. Cet essai puise dans des informations historiques, archéologiques, narratives et philologiques, ainsi que dans le raisonnement technique afin d’identifier un terme nautique pour un élément essentiel du gréement des navires norrois du bas moyen âge. Dit húsasnotra ou simplement snotra, l’objet se révèle être un palan à poulie encastré qui reçoit la drisse. Le palan, en forme de pommeau, fut monté en haut du mât, au-dessus de la seule voile carrée du bateau. Un burr d’un bois dur comme l’érable (nommé dans les textes narratifs), à grain dense et ondoyant, aurait été une matière convenable pour le palan et aurait réalisé des effets ornementaux à un endroit éminent des bateaux de guerre et des navires marchands norrois d’autour de l’année mille.